Folate Metabolism and Human Reproduction - Thaler, C. J. (Geburtshilfe und Frauenheilkunde, 2014)
Folate metabolism affects ovarian function, implantation, embryogenesis and the entire process of pregnancy. In addition to its well-established effect on the incidence of neural tube defects, associations have been found between reduced folic acid levels and increased homocysteine concentrations on the one hand, and recurrent spontaneous abortions and other complications of pregnancy on the other. In infertility patients undergoing IVF/ICSI treatment, a clear correlation was found between plasma folate concentrations and the incidence of dichorionic twin pregnancies. In patients supplemented with 0.4 mg/d folic acid undergoing ovarian hyperstimulation and oocyte pick-up, carriers of the MTHFR 677T mutation were found to have lower serum estradiol concentrations at ovulation and fewer oocytes could be retrieved from them. It appears that these negative effects can be compensated for in full by increasing the daily dose of folic acid to at least 0.8 mg. In carriers of the MTHFR 677TT genotype who receive appropriate supplementation, AMH concentrations were found to be significantly increased, which could indicate a compensatory mechanism. AMH concentrations in homozygous carriers of the MTHFR 677TT genotype could even be overestimated, as almost 20 % fewer oocytes are retrieved from these patients per AMH unit compared to MTHFR 677CC wild-type individuals.
Keywords: assisted reproduction; folate metabolism; homocysteine; human reproduction; folliculogenesis